Elevating brand loyalty: Deciphering the impact of airline service quality and customer satisfaction in Bangkok?s aviation industry: Case study low-cost airlines - Kanchanawongpaisan S.; Zhou F.; Voon B.W.N.; Lu L.; Tan R.S.-E. (EnPress Publisher, LLC, 2025)
This research investigates the relationship between the quality of airline services, customer satisfaction, and brand loyalty with low-cost airlines in Bangkok?s aviation business. It uses structural equation modeling (SEM) to examine the replies of 521 passengers. The study demonstrates a robust and favorable correlation between the quality of service and customer satisfaction, with a direct impact coefficient of 0.961. Furthermore, service quality directly (0.708) and indirectly (0.284) impact brand loyalty. These impacts are mediated by customer satisfaction, which directly affects brand loyalty with a correlation of 0.296. The model explains 92.3% and 99.0% of the variation in customer satisfaction and brand loyalty, respectively, suggesting a robust and reliable match. The demographic study reveals that the predominant group of participants consists of well-educated, middle-income women who regularly use airline services. These results highlight the importance of service quality in improving customer satisfaction and promoting brand loyalty among travelers. Airlines should emphasize the ongoing enhancement of service quality and customer satisfaction to sustain their competitive edge. This research enhances the existing body of knowledge by emphasizing the intermediate function of customer satisfaction and presenting detailed observations relevant to Bangkok?s aviation industry, providing guidance for infrastructural development and investment. It also offers practical suggestions for managing service quality and implementing customer retention strategies. ? 2024 by author(s).